VESICOVAGINAL FISTULA: AN EXPERIENCE OF 30 CASES AT AYUB TEACHING HOSPITAL ABBOTTABAD - Khan, Raza M.; Raza, Nabeela; Jehanzaib, Mohammed; Sultana, Ruqia (Journal of Ayub Medical College Abbottabad, 2005)
Background: Vesicovaginal fistula (VVF) is a disease that is rare in developed world but is frequently seen in poorer countries. It is mostly a result of gynaecological or obstetrical procedures. This study reports our experience of VVF. Methods: This study was carried out at department of Urology, Ayub Teaching Hospital, Abbottabad from June 1998 to June 2004. Detailed history was taken to record age, nature of trauma, time interval of appearance of fistula and previous attempts of repair if any. In addition the results of repair were evaluated. Results: During this six years study period a total of 30 cases of urinary incontinence due to VVF were referred from Gynaecology and Obstetrics department for management, many gave history of birth trauma resulting in leakage of urine per vaginum. Majority of patients with VVF were between 21- 40 years of age. All the patients presented with total incontinence of urine. Most common etiological factor was obstructed labour (63.33%). The other factors were caesarian section (13.33%), hysterectomy (13.33%), forceps delivery (3.33%) and bladder calculus (3.33%). A single case was due to carcinoma cervix and post irradiation (3.33%). Three out of 30 patients had one or more previous fistula repair attempts, while in the rest repair was not attempted before. We carried out transvesical repair in all patients, 80% of patients were completely cured and symptom free, 10% had stress incontinence with frequency of micturition but no vaginal leakage. Failure was 10%. Conclusion: VVF is frequently encountered in Hazara division of Pakistan. It is mostly due to obstetrical causes. Keywords: Vesicovaginal Fistula, urology, incontinence